The Impact of Case-Based Learning on Students’ Critical Thinking: Insights from an Experimental Study - Amelia, Ria; Sukroyanti, Baiq Azmi; Prayogi, Saiful (Lensa: Jurnal Kependidikan Fisika, 2024)
The persistent issue of low critical thinking skills among students in physics education highlights the limitations of traditional teaching methods, which often emphasize memorization over analytical and evaluative thinking. This study investigates the impact of Case-Based Learning (CBL) on improving critical thinking skills, focusing on six indicators: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Conducted at SMA Negeri 1 Kediri, Lombok, Indonesia, the study employed a quasi-experimental pretest-posttest control group design. The experimental group received CBL instruction, while the control group was taught using conventional methods. Data collection involved written essay tests scored using a rubric adapted from the Ennis-Weir Critical Thinking Essay Test, with results analyzed through both descriptive and inferential statistics. Descriptive analysis calculated means, standard deviations, and normalized gains (n-gain), revealing significant improvements in the experimental group across all critical thinking indicators, with n-gain scores categorized as high. Inferential statistical analysis using paired and independent sample t-tests confirmed significant differences in critical thinking skill development between the experimental and control groups. The findings demonstrate that CBL fosters critical thinking by engaging students in real-world scenarios, promoting collaboration, and encouraging reflective reasoning. This study concludes that CBL is an effective pedagogical strategy for addressing critical thinking deficiencies in physics education, bridging the gap between theoretical understanding and practical application. The implications suggest integrating CBL into curricula to enhance students’ cognitive skills, equipping them for academic and professional challenges. Future research should explore CBL’s long-term impacts and adaptability to various subjects and educational contexts, ensuring its broader implementation as a transformative teaching approach.